Abu Al-Hasan â€˜Ali Bin Ibrahim Al-Qummi and the Accusation of TahrÄ«f Al-Qurâ€™Än in Books of Shia Muslims: a Study on the Book Tafsir Al-Qummi - Haq, Muhammad Itsbatul; Halim, Abd. (DINIKA : Academic Journal of Islamic Studies, 2021)
One of the most principal sources of Sunni-Shia conflict is the claim aboutthe presence of'tahrīf Al-Qur'an', or the distortion in the Qur'an, in many Shia literatures of Qur'an exegesis books. The claim ends in causing many Shia Muslims to suffer discrimination. For example, they are believed to have a different version of the Qur’an and the doctrin of taqiyyahwith which they the true nature of their belif. This study focuses on the works of Abu al-Hasan ‘Ali bin Ibrahim al-Qummi which are considered to be the main reference for accusing Shia Muslims of distorting some Qur’anic verses(tahrīf). This study aims to review the thought of al-Qummiabout tahrīf al-Qur’anas he claimed. This is library research using content analysis.The research found that al-Qummiwhen developing the concept of 'tahrīf Al-Qur'an'focused on exegetical exercises, not on actual distortion of the Qur’anic texts.This finding was based on the fact that the term ‘tahrif’ which that some classical ulema (figures) of Shia Muslims made did not deal with distortion of the Qur’anic verses (the corruption of texts), but with Qur’an interpretations which contradict the intended meaning of the Qur’anic verses (the corruption of meaning).